Simulation Of Combined Air-Ground And Solar Heat Exchange System In The Test Room Using CFD - Bastian Resta Pinem (Institute of Computer Science (IOCS), 2021)
In terms of increasing comfort in a room, a lot of research done to create a system that can make the room feel comfortable without having to waste a lot of energy. The energy savings of today are the main priorities due to the limited availability of energy and the unlimited need for energy. The use of air conditioning in terms of increasing comfort in the room, besides wasting much energy, the other side effects of using air conditioning is also create a greenhouse effect for the earth. This research was done to create a couple system between earth air heat exchanger to cool the air in the room and solar chimney which has the role of generating room air ventilation. The main purpose of this research is to create a system that can be used to create a comfortable room without using energy. The simulation of this research using Ansys 19.0 : student version, simulation is done separately with transient method and active radiation function in models. The size of the test room 2 mx 2m x 2m, high solar chimney 5 m, diameter 0.3 m, and 1mm thick, the size of earth air heat exchanger along 26.5 m, diameter 4” and with thickness 3mm. In the simulation result, the system succeeded in decreasing the room temperature up to 27.883oC at simulation and 25.2653 oC on the experimental result whereas in the earth air heat exchanger the outlet temperature was 26.33 oC at simulation, and 27.3507 oC on the experimental results. diameter 4” and with thickness 3mm. In the simulation result, the system succeeded in decreasing the room temperature up to 27.883oC at simulation and 25.2653 oC on the experimental result whereas in the earth air heat exchanger the outlet temperature was 26.33 oC at simulation, and 27.3507 oC on the experimental results. diameter 4” and with thickness 3mm. In the simulation result, the system succeeded in decreasing the room temperature up to 27.883oC at simulation and 25.2653 oC on the experimental result whereas in the earth air heat exchanger the outlet temperature was 26.33 oC at simulation, and 27.3507 oC on the experimental results.